A review on the environment’s influence on coastal marine steel corrosion and in-situ monitoring - Kassinis, Christos; Aresti, Lazaros; Koronides, Marios; Christodoulides, Paul; Michailides, Constantine; Onoufriou, Toula (My University, 2025)
Marine corrosion is a critical subject that holds substantial importance from multiple perspectives, including engineering design, structural safety, and economic sustainability. The harsh marine environment presents unique challenges, as the interaction between steel structures and corrosive elements can lead to significant degradation over time, impacting the performance, reliability, and longevity of critical infrastructure. Understanding the mechanisms and effects of marine corrosion is essential for optimizing design strategies, ensuring safety, and reducing unnecessary costs associated with over-engineering or premature failures. This study seeks to contribute to this understanding by comprehensively reviewing and synthesizing the current body of knowledge available in the literature. It examines the key factors influencing corrosion in marine environments, such as salinity, temperature, and biofouling, and explores their specific effects on steel structures commonly used in marine applications. Additionally, the study highlights the importance of field monitoring techniques, providing an overview of methodologies used to observe and measure corrosion rates in real-world conditions. These techniques are crucial for capturing the dynamic and complex nature of marine corrosion processes and for developing realistic models to predict long-term impacts.
Keywords: Corrosion types; Off-shore structures; Marine corrosion; Corrosion monitoring